Breeding strategies of open-cup-nesting birds in sub-Antarctic forests of Navarino Island, Chile - Jara, Rocío Fernanda; Crego, Ramiro Daniel; Arellano, Francisco Javier; Altamirano, Tomás Alberto; Ibarra, José Tomás; Rozzi, Ricardo; Rozzi Marin, Ricardo Roberto (My University, 2019)
Abstract Background: There is limited knowledge about the breeding strategies of birds inhabiting in South American temperate forests. This is particularly true for open-cup forest passerines breeding at high latitudes (> 42°). To better understand the ecology of these species, in this study we described and compared the breeding strategies (i.e., nest dimensions, nest height from the ground, egg laying rhythm, clutch size, length of the developmental periods, breeding phenology, and diversity of nesting substrate) of five passerine birds that inhabit sub-Antarctic ecosystems. Methods: During three breeding seasons (2014-2017), we monitored 103 nests of the five most abundant open-cup forest-dwelling passerines (Phrygilus patagonicus, Anairetes parulus, Turdus falcklandii, Elaenia albiceps, and Zonotrichia capensis) on Navarino Island (55°S), Cape Horn Biosphere Reserve, southern Chile. Additionally, we compared the breeding strategies of T. falcklandii to another population breeding at lower latitude (39°S). Results: Most of the species started laying eggs the last week of September; only E. albiceps started 2 months later. During the breeding season of 2016-2017 both E. albiceps and Z capensis started laying eggs earlier than the previous year. Anairetes parulus and Z. capensis were the most specialized in terms of nesting substrate. Turdus falcklandii had larger clutch sizes and nested closer to the ground on Navarino Island compared to the northern population, which might put this and other ground nesting species of this island at a higher risk of predation by the recently introduced American mink (Neovison vison). Conclusions: Our five study species breed exclusively in open-cups (not in cavities) in sub-Antarctic forests, and some of them built their nests closer to the ground compared to populations breeding at lower latitudes. This may be associated with the lack of terrestrial predators on Navarino Island. Our study opens further questions about the mechanisms driving differences in breeding strategies among populations.
Keywords: anairetes parulus; elaenia albiceps; latitude; nesting; phrygilus patagonicus; turdus falcklandii; zonotrichia capensis